Morphology and dynamics of the ulnar nerve in the cubital tunnel after percutaneous cross-pinning of supracondylar fractures in children's elbows: an ultrasonographic study - Karakurt, L; Ozdemir, H; Yilmaz, E; Inci, M; Belhan, O; Serin, E (Lippincott Williams & Wilkins, 2005)
After the 12.6-month (3-30) follow-up period, the morphology and dynamics of the ulnar nerve in the cubital tunnel were examined with ultrasonography on operated (group 1) and opposite (group 2) elbows of 13 children who had percutaneous cross-pin fixation for displaced supracondylar humerus fractures. When we compared group 1 and group 2, nerve morphology was similar (P > 0.05), but nerve dynamics were found to be decreased or absent for seven (54%) elbows in group 1 (P < 0.05). The medial K-wire may damage the ulnar nerve dynamics in the cubital tunnel. (c) 2005 Lippincott Williams & Wilkins.
Keywords: medial pin; cubital tunnel; ulnar nerve; ultrasonography; morphology; dynamics